Precision Bathymetric Survey for Marine Infrastructure: A Case Study of Bullnose Jetty, Lagos, Nigeria - Sunday Alademomi, Alfred; Odumosu, Joseph Olayemi; Oladosu, Stephen Olushola (Sriwijaya Journal of Environment, 2026)
The bathymetric survey conducted at Bullnose Jetty, Apapa, Lagos, was an essential preparatory step for ongoing piling and repair activities. This study focused on evaluating seabed conditions along the quay-line to ensure safe engineering practices. Key objectives included the determination of seabed depth relative to average water levels, probing of proposed pile points (A-38_new, A-39_new, A-40_new) for clearance from debris, and identifying the location of a broken pile (A-39). The survey employed advanced equipment, including the South Echo-sounder and GNSS receiver, following systematic methodologies such as vertical accuracy checks, sounding route planning, and echo-sounding operations and videography. Depth measurements were calculated using acoustic signal travel times, with corrections for tidal variations and instrument lag. The 0.1 m grid interval used provided high-resolution data acquisition for the precise mapping of underwater conditions. Findings confirmed the absence of obstructive debris at proposed pile locations and identified the exact position of the broken pile to prevent any interference with repair works. This study showed and recommend the importance of detailed underwater assessments in maintaining marine infrastructure.